(untitled) (PANGEEA, 2025)
This In Memoriam tribute commemorates Ioan Ardelean (1938-2023), a prominent Romanian geographer from Alba County. It outlines his education and long career as a teacher and lecturer (Satu Mare, Carei, Teius, Spiru Haret, Blaj, Alba Iulia), his leadership roles in the Romanian Geographical Society, his political service as a senator, and his extensive publishing activity in geography. The piece also highlights his influence on Romanian geography and his connection to the Pangeea magazine.